Canine prostate cancer cell line (Probasco) produces osteoblastic metastases in vivo. Issue 13 (7th July 2014) - Simmons, Jessica K.; Dirksen, Wessel P.; Hildreth, Blake E.; Dorr, Carlee; Williams, Christina; Thomas, Rachael; Breen, Matthew; Toribio, Ramiro E.; Rosol, Thomas J.
Abstract BACKGROUND In 2012, over 240, 000 men were diagnosed with prostate cancer and over 28, 000 died from the disease. Animal models of prostate cancer are vital to understanding its pathogenesis and developing therapeutics. Canine models in particular are useful due to their similarities to late‐stage, castration‐resistant human disease with osteoblastic bone metastases. This study established and characterized a novel canine prostate cancer cell line that will contribute to the understanding of prostate cancer pathogenesis. METHODS A novel cell line (Probasco) was derived from a mixed breed dog that had spontaneous prostate cancer. Cell proliferation and motility were analyzed in vitro. Tumor growth in vivo was studied by subcutaneous, intratibial, and intracardiac injection of Probasco cells into nude mice. Tumors were evaluated by bioluminescent imaging, Faxitron radiography, µCT, and histology. RT‐PCR and genome‐wide DNA copy number profiling were used to characterize the cell line. RESULTS The Probasco cells grew in vitro (over 75 passages) and were tumorigenic in nude mice. Probasco cells expressed high levels of BMP2, CDH1, MYOF, FOLH1, RUNX2, and SMAD5 modest CXCL12, SLUG, and BMP, and no PTHrP mRNA. Following intracardiac injection, Probasco cells metastasized primarily to the appendicular skeleton, and both intratibial and intracardiac injections produced osteoblastic tumors in bone. Comparative genomic hybridization demonstrated numerous DNA copy number aberrations throughout the genome, including large losses and gains in multiple chromosomes. CONCLUSIONS The Probasco prostate cancer cell line will be a valuable model to investigate the mechanisms of prostate cancer pathogenesis and osteoblastic bone metastases. Prostate 74: 1251–1265, 2014. © 2014 Wiley Periodicals, Inc.